Inhibition of Zbp1-PANoptosome-mediated PANoptosis effectively attenuates acute pancreatitis - Jie Li; Yu-chen Jia; Jiongdi Lu; Haoyu Zhang; Zheng Wang; Xiaozhou Xie; Feng Cao; Fei Li (Cell Death Discovery)
Abstract Early acute pancreatitis is an acute inflammatory disease that involves multiple modes of cell death, including apoptosis, necrotic apoptosis, and pyroptosis in its disease process. PANoptosis, a type of cell death that includes pyroptosis, apoptosis, and necroptosis, has had an important role in a variety of infectious and inflammatory diseases in recent years. To judge the relationship between PANoptosis and AP, we first analyzed the data from pancreatic transcriptome data by bioinformatics techniques, and we found the enrichment of PANoptosis pathway in AP. Next, we screened the genes and identified differentially expressed genes (DEGs) associated with AP and PANoptosis. Finally, we found that Zbp1 may have a major role in the process of PANoptosis. For this purpose, we constructed AP models in mice and in vitro cell line 266-6 and intervened by inhibiting Zbp1. The final results showed that the PANoptosis in mice was significantly suppressed after inhibition of Zbp1. In conclusion, inflammatory injury in AP can be significantly improved by inhibiting Zbp1- PANoptosome-mediated PANoptosis.